Do Molecular Profiles of Primary Versus Metastatic Radioiodine Refractory Differentiated Thyroid Cancer Differ? - Gomes-Lima, Cristiane J.; Shobab, Leila; Wu, Di; Ylli, Dorina; Bikas, Athanasios; McCoy, Matthew; Feldman, Rebecca; Lee, Wen; Rao, Sarika N.; Jensen, Kirk; Vasko, Vasily; Castro, Luiz Claudio; et al. (Frontiers in Endocrinology, 2021)
Management of metastatic radioiodine refractory differentiated thyroid cancer (DTC) can be a therapeutic challenge. Generally, little is known about the paired molecular profile of the primary tumor and the metastases, and whether they harbor the same genetic abnormalities. The present study compared the molecular profile of paired tumor specimens (primary tumor/metastatic sites) from patients with radioiodine refractory DTC in order to gain insight into a possible basis for resistance to radioiodine. Twelve patients with radioiodine refractory metastases were studied; median age at diagnosis of 61 years (range, 25-82). Nine patients had papillary TC (PTC), one had follicular TC (FTC) and two had Hürthle cell TC (HTC). Distant metastases were present in lungs (n=10), bones (n=4) and liver (n=1). The molecular profiling of paired tumors was performed with a panel of 592 genes for Next Generation Sequencing, RNA-sequencing and immunohistochemistry. Digital microfluidic PCR was used to investigate TERT promoter mutations. The genetic landscape of all paired sites comprised BRAF, NRAS, HRAS, TP53, ATM, MUTYH, POLE and NTRK genes, including BRAF and NTRK fusions. BRAF V600E was the most common point mutation in paired specimens (5/12). TERT promoter mutation C228T was detected in one case. PD-L1 expression at metastatic sites was highly positive (95%) for one patient with HTC. All specimens were stable for microsatellite instability testing and the tumor mutation burden was low to intermediate. Therefore, the molecular profile of DTC primary and metastatic lesions can show heterogeneity, which may help explain some altered responses to therapeutic intervention.